Políticas públicas de manejo de águas pluviais em Belo Horizonte: novos caminhos em meio a velhas práticas - Cristiane Borda Pinheiro (2019)
In the second half of the twentieth century, a broad contestation of the model of urbanization adopted from the mid-nineteenth century by modern society emerged in the wake of the environmental movement. In this context, a new paradigm for urban stormwater management has been formulated in developed countries to mitigate the impacts generated by cities on the terrestrial hydrological cycle, through an integrated approach off the river basin - a fundamental unit of analysis and design -, sectoral policies, socio-environment and urban actors. This research aimed to identify the challenges for the implementation of this emerging paradigm in the contemporaneity regarding the urban stormwater management in the Brazilian context. Although the environmental discourse on the valorization of urban waters is widely diffused in the country, the works are mainly oriented by the traditional concept of urban drainage, based on the hygienist bias of channeling water courses and rapid evacuation of stormwater. It was discussed the incorporation of fundamental concepts of hydrology in the field of urban planning and management, from a critical view of sustainable development and integration between city and nature. An analysis of the recent experience of Belo Horizonte, a city that in the last 20 years has developed public policies to mitigate the impacts of urbanization on the hydrological cycle, although still very restricted, was carried out. Various legal instruments and institutional arrangements, as well as plans, programs, projects and works were raised and related to compose the panorama of these public policies and indicate the possibilities that they launch for future guidelines of intervention in this field. The research strategy combined the case study, interpretive-historical and qualitative methods. Data were collected through consultation of documents, participation in events, visits to public works and interviews with key actors.